2016
DOI: 10.2174/1874285801610010168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in Mouse Model of Combined Virus-bacterial Vaccine Based on Attenuated Influenza A(H7N3) Virus and the Group B Streptococcus Recombinant Polypeptides

Abstract: Background:Secondary bacterial influenza complications are a common cause of excesses morbidity and mortality, which determines the need to develop means for specific prophylaxis. Group B streptococcal infection is especially common cause of pneumonia among children and the elderly with underlying conditions. Here we investigate in a mouse model the effects of combined intranasal immunization using live attenuated influenza vaccine and recombinant polypeptides based on group B Streptococcus surface proteins.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The titers of IgG antibodies to the viruses A/H7N3 and A/H7N9 but not to A/H1N1 significantly increased by the 21st day after immunization, compared with day 5 (P < 0.001). This data confirm the previously obtained results on the immunogenicity of an associated vaccine based on LAIV and recombinant GBS polypeptides [1, 2]. Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The titers of IgG antibodies to the viruses A/H7N3 and A/H7N9 but not to A/H1N1 significantly increased by the 21st day after immunization, compared with day 5 (P < 0.001). This data confirm the previously obtained results on the immunogenicity of an associated vaccine based on LAIV and recombinant GBS polypeptides [1, 2]. Fig.…”
Section: Resultssupporting
confidence: 93%
“…Associated viral-bacterial intranasal immunization based on live influenza vaccines (LAIV) and recombinant bacterial polypeptides (either by simple mixing of preparations or by creating genetically engineered constructions) is a new direction of vaccine prophylaxis, which allows to reach the protective effect against post-influenza bacterial complications by one vaccination. This effect is achievable both due to the reduction of the primary viral infection, and through the formation of specific antibodies against bacterial polypeptides [1]. For the prevention of respiratory infections, it is important to develop mucosal vaccines to stimulate not only systemic but also local humoral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we have shown that associated intranasal immunization of outbred mice using live attenuated influenza vaccine (LAIV) of H7N3 subtype and 4 GBS recombinant polypeptides was effective against pulmonary infection with five hundred 50% mouse infectious doses (MID 50 ) of avian A/mallard/ Netherlands/12/00(H7N3) or 100 MID 50 A/PR8/34(H1N1) influenza followed by GBS serotype II secondary infection. 13 In this study, we evaluated whether immunity generated against H7N3 LAIV and GBS polypeptides can protect against H7N9 influenza infection followed by GBS burden. We also made an attempt to reveal the role of some causes of innate and adaptive immunity in such protection.…”
Section: Prevention Of Influenza A(h7n9) and Bacterial Infections In mentioning
confidence: 99%
“…Previously, we proved the effectiveness of mixed immunization against influenza and group B Streptococcus in alleviating the course of a virus-bacterial co-infection. A mixture of live influenza vaccine and several polypeptides, recombinant analogs of group B streptococcal surface proteins, was successfully used as a vaccine preventing the GBS infection [5,6]. In the present work we employed a mixture of live influenza vaccine and PSPF protein, a genetically engineered preparation against pneumococcal infection, for vaccination.…”
Section: Introductionmentioning
confidence: 99%